Knowledge and awareness of pulp vitality tests among dental interns and postgraduates: A multicenter cross-sectional study - Kanamarlapudi Venkata Saikiran; Deepa Gurunathan; Sainath Reddy Elicherla; Shaik Rahul; Sailavanya Nuvvula; Sivakumar Nuvvula (Wolters Kluwer Medknow Publications, 2024)
Aim: The aim of this study was to assess knowledge and awareness on pulp vitality tests among dental interns and postgraduate (PG) students. Methods: Using a standardized approach and employing focus group discussions, a 13-item questionnaire was developed. The questionnaires were shared with dental interns and PGs of various dental colleges through WhatsApp and their registered e-mail addresses as a Google Form link. Data from all the individuals were collected to assess and compare the knowledge among dental interns and PG students. Results: During 4 weeks, 358 of the total 428 responses were received. The final analysis was carried out using 340 responses (145 PG [42.6%] and 195 intern [57.4%] responses), of which 18 were excluded due to repeated responses. More than half of the participants needed more knowledge about pulp vitality testing. Conclusion: Dental PG students had better knowledge and awareness than interns, but implementing this in practice was relatively negligible. Knowing the importance of comprehending pulp vitality tests may aid students in reducing the possibility of damaging the healthy structure of the teeth.